Studies of ultrafast molecular dynamics by femtosecond extreme ultraviolet absorption spectroscopy - Loh, Zhi-Heng (2022)
Transient absorption spectroscopy is one of the most widely used experimental techniques for time-resolved studies of ultrafast phenomena. Recent advances in the generation of short-wavelength pulses of ultrashort duration have made transient absorption probing of atomic core level transitions possible. In this Highlight Review, we introduce our recent work on using extreme ultraviolet (XUV) transient absorption spectroscopy to investigate the ultrafast molecular dynamics induced by intense laser fields. While investigations of intense laser-molecule interaction have primarily focused on elucidating electron dynamics, it is important to understand the vibrational dynamics that are triggered by intense laser fields because of their coupling to electron dynamics. Probing the iodine 4d core level, our XUV transient absorption studies of iodoalkanes irradiated by intense laser fields elucidate ultrafast dissociative ionization dynamics and vibrational wave packet dynamics. Time-dependent XUV spectral shifts and global analysis of time-resolved XUV transient absorption spectra can be used to reconstruct CI dissociation dynamics and identify multiple dissociation channels. In addition, XUV transient absorption spectroscopy also unravels both small- and large-amplitude coherent vibrational motion, whose origin can be identified by analyzing the phase of the oscillatory XUV transition energies. Our studies show that XUV transient absorption spectroscopy is a powerful technique for the study of ultrafast molecular dynamics.